Efficient photocatalytic degradation of acrylonitrile by Sulfur-Bismuth co-doped F-TiO2/SiO2 nanopowder. (June 2020) - Li, Hanliang; Qiu, Lu; Bharti, Bandna; Dai, Fangwei; Zhu, Manyu; Ouyang, Feng; Lin, Lin
Abstract: In this study, a simple sol-gel method was applied for preparing effectual photocatalyst of S-Bi co-doped F-TiO2 /SiO2 (S-Bi-F-TiO2 /SiO2 ) nanopowder. Optimal preparation conditions were obtained by optimizing the calcination temperature and the ratio of S and Bi. The synthesized powder was characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), energy dispersive spectrometer (EDS), X-ray photoelectron spectroscopy (XPS), brunauer-emmett-teller (BET), UV–Visible diffuse-reflectance spectroscopy (UV–Vis DRS), photoluminescence spectroscopy (PL) and ammonia adsorption and temperature-programmed desorption (NH3 -TPD). The photocatalytic activity was evaluated by the degradation of acrylonitrile under simulated visible light irradiation. S-Bi-F-TiO2 /SiO2 nanopowder possess excellent photocatalytic properties under visible light for the degradation of acrylonitrile, when the calcination temperature was 450 °C for 2 h and the ratio of S and Bi was 0.02: 0.007. The degradation efficiency of acrylonitrile reached to 81.9% within 6 min of visible light irradiation. Compared with F-TiO2 /SiO2 sample, NH3 -TPD and PL results revealed the higher photocatalytic activity for S-Bi-F-TiO2 /SiO2, which is mainly due to the increase strength and number of surface acid site with S doping. The co-doping with S & Bi improved the separation of electron-hole pairs and enhanced the photocatalytic oxidizing species. The UV–Vis DRS showed stronger absorption in S-Bi co-doped F-TiO2 /SiO2 catalyst as compared to F-TiO2 /SiO2 catalyst. XPS results demonstrated the presence of various surface species viz. oxygen vacancies, Ti 3+, Ti 4+, O 2− and OH group. Graphical abstract: Image 1 Highlights: Sulfur- Bismuth codoped F-TiO2 /SiO2 photocatalyst was prepared by sol-gel method. S doping increases acid strength and enhance absorption in visible region. Bi doping mainly inhibits the recombination of photogenerated electron-hole pairs. S-Bi-F-TiO2 /SiO2 photocatalyst shows superior photocatalytic activity.